Information Literacy For The Net Generation To Anticipate The Danger Of Intolerance - Heni Nuraeni Zaenudin; Suwatno . (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
Intolerance behaviors that are not anticipated may give birth to the danger of radicalism both psychologically and physically.  This study aims at exploring the way to select and discover informational sources related to the topics; at investigating a means of estimating, accepting, and determining the best thing in the future; at analyzing a means of building new knowledge associated with gained information; and discovering a means of providing and broadcasting information on the website.  This study used case study method in order to observe the reality of information literacy and the danger of intolerance among the net generation Observation findings show that the doctrine of intolerance was spread through group discussions of religious Student Activity Unit (UKM). The massive spread of radical viruses is supported by the dominance of the internet as the main medium in information searching. The condition is made worse by low information literacy skills. The results of this study expected to be able to be used as references relating to information literacy for the net generation to anticipate the danger of intolerance which is the forerunner of radicalism. The results showed that the low reading abilities led to a conservative interpretation of religious meanings, which considered one’s understanding more correct and accused others as infidels. This phenomenon can be seen from the discovery of limited new knowledge. Hence, the knowledge of information literacy must be introduced in lecture rooms and within intra-university activities.